KONSEP PEMBANGUNAN HUKUM E-COMMERCE - Hidayah, Ardiana (Solusi, 2019)
The development of transportation, communication and information technology further increases the pace of globalization. The use of technology has driven business growth including transaction activities by utilizing technology and telecommunications through e-commerce activities. Problem formulation related to the application of business law in e-commerce activities and the role of law and the concept of legal development in e-commerce business. Legislation in e-commerce activities has been regulated in Law Number 11 of 2008 which has been amended into Law Number 19 of 2016 concerning Information and Electronic Transactions, Law Number 7 of 2014 concerning Trade and Government Regulation Number 82 In 2012 concerning the Implementation of Electronic Transactions and Systems. In its application there are still some weaknesses, namely the existence of objects in electronic transactions cannot be perfectly perceived electronically. There are still obstacles to accountability and the level of reliability in proof of an electronic contract. Law is a tool for maintaining order in society. Law will always adjust to the conditions that occur in the middle of the community and act as a means of renewal in people's lives. Rapid development has resulted in increasingly complex problems faced by the community from traditional patterns to modernization. The development of business law in Indonesia in e-commerce activities is carried out to support the realization of sustainable economic growth, as well as creating certainty, enforcement and legal protection.